Effect of Detergent Concentration and Exposure Duration on the Growth of Heterotrophic Bacteria in Seawater - Hafizh, Muhammad; Effendi, Irwan; Zulkifli, Zulkifli (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
This research was conducted from June to July 2024 at the estuary of the Selat Morong River, Rupat District, Bengkalis Regency, Riau Province. This study aimed to examine the effect of different detergent concentrations on the growth of heterotrophic bacteria, as well as to investigate the influence of varying detergent exposure durations on their growth. The experimental method employed a two-factor completely randomized design (CRD) consisting of different detergent concentrations (Factor A) with five levels: A1 (0 ppm) as the control, A2 (3000 ppm), A3 (6000 ppm), A4 (9000 ppm), and A5 (12,000 ppm), and varying exposure durations (Factor B): 1 day, 6 days, 11 days, 16 days, and 21 days. The results showed that the logarithmic values of heterotrophic bacterial growth over the 21 days indicated the highest growth occurred on day 1 at a concentration of 0 ppm, with a value of 7.09 CFU/mL. However, bacterial growth declined over time, reaching its lowest point on day 11 at a concentration of 3000 ppm, with a value of 6.95 CFU/mL. Statistical analysis revealed that different concentrations and exposure durations had no statistically significant effect on the growth of heterotrophic bacteria (P>0.05), meaning that variations in detergent concentration and exposure time did not cause meaningful differences in bacterial growth under the experimental conditions. This study highlights the potential resistance of heterotrophic bacteria to detergent exposure. It provides a basis for further research into the resilience of microbial communities in marine environments affected by pollution.